2013
DOI: 10.1002/app.39235
|View full text |Cite
|
Sign up to set email alerts
|

Preparation and evaluation of radioiodinated thermoresponsive polymer based on poly(N‐isopropyl acrylamide) for radiotherapy

Abstract: A thermoresponsive polymer based on poly N-isopropylacrylamide (PNIPAM) was synthesized and radioiodinated to explore its potential use in localized radiotherapy. The synthesized PNIPAM polymer was functionalized with L-tyrosinamide to facilitate radioiodination. The content of tyrosinamide groups in the polymer was assayed spectrophotometrically (k ¼ 275nm). The functionalized polymer showed a cloud point temperature of 29-31 C and phase separation at 35 o C, as revealed by Differential Scanning Calorimetry (… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2014
2014
2020
2020

Publication Types

Select...
2
2

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(3 citation statements)
references
References 36 publications
0
3
0
Order By: Relevance
“…34 The strong bands at 1261 and 802 cm 21 were attributed to the CAOAC stretching vibrations in epoxy group, 35,36 and the strong bands at 1095 and 1022 cm 21 were assigned to the CAO stretching vibrations. [37][38][39] These indicated that there was epoxy sizing agent on CF. As shown in FESEM images of untreated CF and acetone-treated CF, CF became smooth after treated by acetone.…”
Section: Resultsmentioning
confidence: 99%
“…34 The strong bands at 1261 and 802 cm 21 were attributed to the CAOAC stretching vibrations in epoxy group, 35,36 and the strong bands at 1095 and 1022 cm 21 were assigned to the CAO stretching vibrations. [37][38][39] These indicated that there was epoxy sizing agent on CF. As shown in FESEM images of untreated CF and acetone-treated CF, CF became smooth after treated by acetone.…”
Section: Resultsmentioning
confidence: 99%
“…Hydrogels based on PNIPAAm have been studied extensively for drug‐delivery applications . The release of drugs in a sustained manner is one of the most important concerns in drug‐delivery systems.…”
Section: Introductionmentioning
confidence: 99%
“…Hydrogels based on PNIPAAm have been studied extensively for drug-delivery applications. [9][10][11][12] The release of drugs in a sustained manner is one of the most important concerns in drugdelivery systems. However, hydrogels typically release drugs, especially proteins, by rapid diffusion in an initial short-lasting burst, which is followed by a slow and relatively constant release rate.…”
Section: Introductionmentioning
confidence: 99%